Assessment of Water Quality Status and Pollution Index in Musi River, South Sumatera, Indonesia - Muhammad Rendana; Yandriani; Puspa Ayu Pitayati; Muhammad Izzudin; Mona Lestari (Indonesian Journal of Environmental Management and Sustainability, 2022)
A study area was at the Musi River, located in the southern part of Sumatera Island, Indonesia. This river flows in the southern area with a majorly tropical rainforest climate. For decades, it has become a substantial port used mainly for the transport of rubber, petroleum, and oil palm, which has the potential to threaten the area. Therefore, the objective of this study was to investigate the impacts of these activities by evaluating the water quality status and pollution index in the Musi River. Physicochemical parameters such as pH, salinity, temperature, dissolved oxygen (DO), biological oxygen demand (BOD), chemical oxygen demand (COD), and total suspended solids (TSS) were measured along the river. Results of the study revealed the impact of agriculture and fish farming activities in the upstream area has affected the pH values of the water became slightly acidic. In addition, COD values at all stations were found to be high and made they could not be used for drinking water. TSS values were also found to be high at the downstream stations. According to the pollution index status, the study area was classified from low to moderate pollution.